Evaluating Training Effectiveness Using the Malaysian Sample: Tracing the Mediation Effect of Training Motivation Using SEM-AMOS - Abdul Aziz, Siti Fardaniah (International Journal of Economics and Financial Issues, 2016)
A large number of researches indicated that training motivation as the mediator on the relationship between independent variables and training effectiveness. Interestingly, various factors were indicated to stimulate training motivation and effectiveness; however the interaction between these variables has received little attention. Hence, the aim of this study was to determine the interaction between variables related to training effectiveness, especially the mediation effect of training motivation. Using samples of participants attended compulsory training to obtain certificate for practice organized by the Malaysian NIOSH (National Institute of Occupational Safety and Health) in 2015; findings indicated that training motivation only mediated the relationship between training-characteristic support and training effectiveness with a large effect. However, there is a chain-linkage relationship between these variables; findings were supported by previous research. Hence, findings can be used for planning intervention to improve training effectiveness and organizational performance in the global economy context. Keywords: comprehensive training motivation; training effectiveness; employee training; Malaysia JEL Classifications: J24; M53; M54